Hate Speech and Freedom of Speech. A Cultural and Anthropological Conceptual Frame - Płuciennik, Jarosław; Wróblewski, Michał (Hassrede – ein multidimensionales Phänomen im interdisziplinären Vergleich, 2020)
The article is a review of topics, critical trends and methodological discourses among young researchers dealing with the issue of hate speech and the phenomenon of hate itself, which are particularly connected with communication in the Network and the networked society. The analysis was carried out based on current texts published in the monograph from 2017 Hejterstwo – nowa praktyka kulturowa? Geneza, przypadki, diagnozy. In the paper we present the interpretation of research trends in the humanities and socio-political sciences in the light of history of ideas related to freedom of speech.